2005
DOI: 10.1128/cdli.12.9.1063-1068.2005
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Immunoglobulin G1 Directed againstAspergillus fumigatusCell Wall Glycoprotein Protects against Experimental Murine Aspergillosis

Abstract: Most of the biological functions related to pathogenicity and virulence reside in the fungal cell wall, which, being the outermost part of the cell, mediates the host-fungus interplay. For these reasons much effort has focused on the discovery of useful inhibitors of cell wall glucan, chitin, and mannoprotein biosynthesis. In the absence of a wide-spectrum, safe, and potent antifungal agent, a new strategy for antifungal therapy is directed towards the development of monoclonal antibodies (MAbs). In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 41 publications
2
45
0
1
Order By: Relevance
“…Several studies have suggested a possible protective role for antibodies in immunity against fungal diseases, in particular for yeast infections such as cryptococcosis (35) and candidiasis (11,27,35,39,48,49) and a few for aspergillosis, a mold infection (12,13). Interestingly, most studies were conducted in vitro or used animal models of systemic disease, in which fungal spores were intravenously injected, which is quite different from the respiratory route of naturally occurring aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a possible protective role for antibodies in immunity against fungal diseases, in particular for yeast infections such as cryptococcosis (35) and candidiasis (11,27,35,39,48,49) and a few for aspergillosis, a mold infection (12,13). Interestingly, most studies were conducted in vitro or used animal models of systemic disease, in which fungal spores were intravenously injected, which is quite different from the respiratory route of naturally occurring aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to GXM have been characterized as potential therapeutic agents (6) and are in clinical trials for individuals with cryptococcosis (18). In other models, passively administered MAbs have protected mice against lethal infections with Histoplasma capsulatum (26), Candida albicans (15), and Aspergillus fumigatus (7). The mechanisms of MAb-mediated protection are complex and heterogeneous, but it appears that passively administered antibodies enhance the effectiveness of host immune cells (5,13) or are directly antifungal (23,35).…”
mentioning
confidence: 99%
“…It is noteworthy that the new monoclonal antibody against A. fumigatus, MAb MPS5.44, was found to have in itself some protective effect, as had previously been reported for other monoclonal antibodies (9). Our MAb was also found to crossreact with other Aspergillus species, such as A. niger, A. flavus, and A. terreus, though it did not recognize C. albicans, C. krusei, or a Mucor mold.…”
Section: Discussionmentioning
confidence: 58%
“…Most are based on azoles, such as voriconazole (52), or on formulations and applications of AMB (6,31,41) or echinocandins (12,16,23). Recent studies of animal models have demonstrated the therapeutic potential of monoclonal antibodies (9,53) as well as of ultrashort synthetic lipopeptides (54) with several types of fungal infections. Another report indicated that anti-idiotypic antibodies administered intranasally could effectively control A. fumigatus infection in neutropenic mice (8).…”
Section: Discussionmentioning
confidence: 99%